Peran Ekonomi Syariah dalam Pengelolaan UMKM Berbasis Media Sosial - Alfiah Thalia Nabila Putri; Herlina Yustati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to analyze the role of sharia economics in the management of social media-based Micro, Small and Medium Enterprises (UMKM). The development of information technology, especially social media, has opened up new opportunities for MSMEs to access wider markets. However, amidst the dynamics of the digital market, the application of sharia economic principles in managing social media-based MSMEs is very important to maintain business sustainability and ensure fair and transparent transactions.. By implementing business models such as mudharabah and musyarakah, social media-based UMKM can optimize financing potential without dependence on interest, as well as strengthen relationships with customers through ethical transactions. The research results show that the application of sharia economics in managing social media-based MSMEs not only improves business performance, but also has a positive impact on brand strengthening, customer loyalty and social empowerment. However, the main challenge in implementing sharia economics in social media-based MSMEs lies in the limited education and understanding among business actors.